2014
DOI: 10.20882/adicciones.131
|View full text |Cite
|
Sign up to set email alerts
|

El modelo de los cinco grandes factores de personalidad y el uso problemático de Internet en jóvenes colombianos

Abstract: Test (Young, 1998), para determinar el grado de uso de Internet (controlado, problemático o adictivo). Los resultados revelaron que el 9.7% de la muestra presenta un uso problemático de Internet.Este porcentaje era en su mayoría masculino (χ 2 = 12.93; p= 0.01) y realizaba actividades de comunicación y ocio. El uso problemático correlaciona positivamente con neuroticismo y negativamente con afabilidad y responsabilidad. Por otra parte, no tiene relación con extraversión y apertura a la experiencia. Ser mujer y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
25

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
2
13
0
25
Order By: Relevance
“…The problematic use of the Internet and SNS usually affects populations who are vulnerable because of their age, such as adolescents (Griffiths and Wood, 2000; Pallanti et al, 2006; Puerta Cortés and Carbonell, 2014). Previous studies have indicated that 2 to 15% of adolescents use the Internet and SNS in an excessive and problematic way (Park et al, 2008; Durkee et al, 2012; Sasmaz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The problematic use of the Internet and SNS usually affects populations who are vulnerable because of their age, such as adolescents (Griffiths and Wood, 2000; Pallanti et al, 2006; Puerta Cortés and Carbonell, 2014). Previous studies have indicated that 2 to 15% of adolescents use the Internet and SNS in an excessive and problematic way (Park et al, 2008; Durkee et al, 2012; Sasmaz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The use that teenagers make or are able to make of Internet is a topic of concern in Spain and elsewhere (Oliva et al, 2012;Puerta-Cortés & Carbonell, 2014;Ruiz-Olivares, Lucena, Pino, & Herruzo, 2010;Smahel et al, 2012;Tsitsika, Tzavela, Mavromati and EU consortium NET ADB, 2012;Valedor do Pobo, 2011). This general concern has been heightened in recent years by the sometimes sensationalist way in which the subject is treated in the media.…”
Section: Resumen Adicciones Vol 27 Issue 1 · 2015 Originalmentioning
confidence: 99%
“…The Web provides access to multiple sources of information, learning, leisure and personal, academic and professional development, as well as to innovative forms of communication, relation and expression. Without questioning its benefits, we should not overlook the fact that its use also involves certain associated risks and dangers (loss of privacy, contact with strangers, isolation), in addition to disconcerting practices such as cyberbullying, grooming or sexting, which are affecting increasing numbers of adolescents, considered one of the most vulnerable groups in this new environment (Castellana, Sánchez-Carbonell, Graner, & Beranuy, 2007;Echeburúa & Corral, 2010;Yang & Tung, 2007).The use that teenagers make or are able to make of Internet is a topic of concern in Spain and elsewhere (Oliva et al, 2012;Puerta-Cortés & Carbonell, 2014;Ruiz-Olivares, Lucena, Pino, & Herruzo, 2010;Smahel et al, 2012; Tsitsika, Tzavela, Mavromati and EU consortium NET ADB, 2012; Valedor do Pobo, 2011). This general concern has been heightened in recent years by the sometimes sensationalist way in which the subject is treated in the media.…”
mentioning
confidence: 99%
“…Actualmente, el uso problemático de Internet se relaciona con el número de horas dedicado por ejemplo a las redes sociales, chat, páginas de contenido para adultos y películas (Carbonel et al, 2012;Oliva et al, 2014;Puerta-Cortés y Carbonell, 2014). Algunos trabajos de investigación señalan que jóvenes universitarios con un uso problemático de Internet presentaban una puntuación alta en rasgos de la personalidad como el neuroticismo, y baja puntuación en rasgos como la afabilidad y la responsabilidad (Kuss, Van Rooij, Shorter, Griffiths y Van de Mheen, 2013;Oliva et al, 2014;Puerta-Cortés y Carbonell, 2014).…”
Section: Introductionunclassified
“…Algunos trabajos de investigación señalan que jóvenes universitarios con un uso problemático de Internet presentaban una puntuación alta en rasgos de la personalidad como el neuroticismo, y baja puntuación en rasgos como la afabilidad y la responsabilidad (Kuss, Van Rooij, Shorter, Griffiths y Van de Mheen, 2013;Oliva et al, 2014;Puerta-Cortés y Carbonell, 2014). Sin embargo, la dificultad de delimitar conceptualmente este comportamiento anormal ha hecho que la más reciente revisión del Manual Diagnóstico y Estadístico de Trastornos Mentales (DSM-V) de la American Psychiatric Association (APA, 2013) no incluya como patología la adicción a Internet.…”
Section: Introductionunclassified